Mixing-sequence controlled selective localization of carbon nanoparticles in PLA/PCL blends - de Aguiar J.* (2019)
© 2018 Society of Plastics EngineersThis work proposes modifying the adding sequence of components during the production of poly(lactic acid) (PLA) and poly(ε-caprolactone) (PCL) ternary systems with multiwalled carbon nanotubes (CNT) or graphene nanoplatelets (GN), in order to analyze the nanoparticles’ selective localization in terms of the competition between different factors, such as kinetics, thermodynamics, rheology, and geometry. In the studied system, the PLA's viscosity is higher than the PCL's and the difference in interactions between the CNT or the GN/PLA and the CNT or the GN/PCL is small, meaning the viscosity effects could dominate. However, other factors, such as thermodynamics and geometry, can be observed to compete with the rheological factor, depending on the mixing sequences. Depending on the processing time, a competition between thermodynamics and rheological factors could be observed when the nanoparticles had contact first with the thermodynamically favored phase. The competition between geometrical and rheological factors was observed in the presence of GN in the PLA phase, in the system in which the GN was added first to the PLA phase, which is the phase of lowest affinity. POLYM. ENG. SCI., 59:323–329, 2019. © 2018 Society of Plastics Engineers.